Studying the impact of different additives on the properties of straight-run diesel fuels with various hydrocarbon compositions - Kirgina M. V. Mariya Vladimirovna; Bogdanov I. A. Ilya Aleksandrovich; Altynov A. A. Andrey Andreevich; Belinskaya N. S. Natalia Sergeevna; Orlova A. Alina; Nikonova N. P. Njurguyaana Pavlovna (2020, 2020)
Title screen